PENGARUH KOMPLEKSITAS TUGAS, PENGALAMAN AUDITOR DAN FEE AUDIT TERHADAP KUALITAS AUDIT DENGAN REMOTE AUDIT SEBAGAI PEMEDIASI PADA AUDITOR KANTOR AKUNTAN PUBLIK DI KOTA SURABAYA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2023)
This research was conducted to determine whether remote audit as a mediating variable can influence the independent variable on the dependent variable. This research was conducted at a Public Accounting Firm in the city of Surabaya, with 44 auditors as the research sample. Testing the hypothesis in this study uses analysis on the Smart-PLS 4.0 application with the Outer Model and Inner Model Test. The results of the study show that Task Complexity, Auditor Experience have a direct influence on remote audits and Audit Fees do not have a direct effect on Remote Audits. The complexity of the duties and experience of the auditor also has an influence on audit quality. Meanwhile, Audit Fee has no influence on Audit Quality. Remote Audit has a negative influence on Audit Quality. Then as a mediating variable Remote Audit has no mediation properties, in which the presence or absence of this mediating variable does not affect the independent variable on the dependent variable. Keywords: Auditor, Task Complexity, Auditor Experience, Audit Fee, Remote Audit, Audit Quality